IMPACT OF SUBJECT CHANGES AT DINIYAH ISLAMIC BOARDING SCHOOL - Hadi, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this writing is to find out: (1) The impact of changing subjects on learning planning at Madrasah Diniyah Pondok Pesantren Miftahul Midad Lumajang. (2) The impact of changing subjects on the learning process at Madrasah Diniyah Pondok Pesantren Miftahul Midad Lumajang. (3) The impact of changes in subject matter on learning outcomes at Madrasah Diniyah Pondok Pesantren Miftahul Midad Lumajang. This study uses a type of field research with a qualitative research design. The results showed that changes in subjects from the 2014-2015 school year to the 2022-2023 school year led to improvements in the subject structure in the form of adding subjects at the Ibtidaiyah and Tsanawiyah levels. Increasing the quantity and quality of subjects at both levels has an impact on problems: (1) equating teaching material in one subject with different teachers at each level, (2) study time and, (3) assessment of learning outcomes. Alternatives taken by madrasah diniyah to overcome this problem while improving the quality of learning are pursued through new policies by forming: (1) subject teacher meetings, (2) scheduling rote submissions once every two weeks and (3) forming Takhossus Kitab Kuning and Reading Al-Quran classes Koran. The process of changing subjects is carried out based on the evaluation results which are routinely carried out at the end of each school year